Were the Ancient Coast Salish Farmers? A Story of Origins. Issue 3 (July 2021) - Lyons, Natasha; Hoffmann, Tanja; Miller, Debbie; Martindale, Andrew; Ames, Kenneth M.; Blake, Michael
Abstract : Were the ancient Coast Salish farmers? Conventional anthropological wisdom asserts that the ethnographically known communities of the Northwest Coast of North America were "complex hunter-fisher-gatherers" who lacked any form of concerted plant food cultivation and production. Despite decades of extensive ethnobotanical and paleoethnobotanical study throughout the Pacific Northwest demonstrating the contrary, this "classic anomaly" is still a cornerstone of anthropological and archaeological canons. The recent discovery of a spectacularly preserved wetland wapato (Indian potato, Sagittaria latifolia ) garden, built 3, 800 years ago in Katzie traditional territory near Vancouver, British Columbia, has helped recast this picture, alongside evidence for other forms of resource management practiced by Northwest Coast peoples. This article examines "origins of agriculture" stories from three distinctive perspectives: Coast Salish Katzie people who cultivated wapato for millennia; settlers who colonized the Fraser River Delta historically, bringing with them their own ideas about what constitutes farming; and archaeologists, who are challenged by these data to reevaluate their own understandings of these cultural constructs. These perspectives have critical bearing on the historical appropriation of lands and waterways by settler communities in British Columbia as well as contemporary questions of sovereignty and stewardship in this region and well beyond.